The effects of zinc supplementation on inflammatory parameters in pregnant women with impaired glucose tolerance: a randomized placebo controlled clinical trial - Roshanravan, Neda; Tarighat-Esfanjani, Ali; Mesri Alamdari, Naimeh; Kheirouri, Sorayya; Mousavi, Reihaneh; Alizadeh, Mohammad (Progress in Nutrition, 2018)
Pregnancy is hyperglycemic cycle of life and usually associated with insulin resistance from mid- gestation. Previous studies indicate that abnormal production of some proteins secreted from adipocytes (adipokines) encloses in pathogenesis of insulin resistance and gestational diabetes mellitus (GDM). It is proven that maternal zinc deficiency affects glucose metabolism, but the interaction between zinc and adipokines secretion are not well understood. This study aims to evaluate the effect of zinc supplementation on Vaspin and IL-6 levels in pregnant women with impaired glucose tolerance (IGT). In this matched, placebo controlled double blind clinical trial, 46 pregnant women with impaired glucose tolerance were randomly distributed to zinc (n=23) and placebo (n=23) groups and received 30 mg/day zinc gluconate or placebo for eight regular weeks. The study was conducted in Shabestar district, North West of Iran. Serum Vaspin and IL-6 levels were assessed before and after intervention. There was a significant decrease in Vaspin and IL-6 levels in zinc group (p= 0.004, p= 0.034, respectively). Further, changes in fasting Vaspin levels had a positive correlation with change in fasting IL-6 levels in both zinc (r= + 0.820, p